2009
DOI: 10.1007/s10103-009-0708-x
|View full text |Cite
|
Sign up to set email alerts
|

Argon ion laser and halogen lamp activation of a dark and light resin composite: microhardness after long-term storage

Abstract: Light-activation significantly influenced the Knoop microhardness values for the darker nanofilled resin composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
9
1
Order By: Relevance
“…19 In another study, a 37.4 KHN and a 48.6% degree of conversion were reported for the Filtek Supreme-A3 activated with a QTH lamp; these values were considerably lower than the values observed in the present study due to the saturation of the nanofilled resin chosen. 8 The translucent resin (shade YT) showed no statistical differences between QTH or LED activation, and these results are similar to those of the present study, which showed similar KHN values independently of the light source.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…19 In another study, a 37.4 KHN and a 48.6% degree of conversion were reported for the Filtek Supreme-A3 activated with a QTH lamp; these values were considerably lower than the values observed in the present study due to the saturation of the nanofilled resin chosen. 8 The translucent resin (shade YT) showed no statistical differences between QTH or LED activation, and these results are similar to those of the present study, which showed similar KHN values independently of the light source.…”
Section: Discussioncontrasting
confidence: 69%
“…A Knoop diamond indenter was used to make fi ve indentations in the center of the surface opposite to the light-irradiated surface of the specimen with a 25 g load for 20 s. 8,19 The mean of the fi ve microhardness evaluations of each specimen was used as the specimen's microhardness value.…”
Section: 19mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Thermal cycling, 2,3,5,6,14 storage of the dry material at 37 o C in acids, and immersion in water, artificial saliva, or hot water [1][2][3][4]7,16 are some of the Graph 1 -Failure mode distribution according to surface treatment and repair and mechanical assay methodology.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Studies have investigated the bonding strength of repairs of aged composites through thermal cycling 2,3,5,6 and immersion in hot water, acids, 2,3 water, or artificial saliva 1,4 for relatively short periods (24 h and 6 mos). [1][2][3][4][5]7 However, studies are needed to determine the behavior of repairs bonded to aged restorations for a longer period of time and the behavior of this repair subjected to the same aging period.…”
Section: Introductionmentioning
confidence: 99%